ENT 300 : Elite Ort Enterprise / Nor Shazana Mohamad Shafiee ... [et al.] - Mohamad Shafiee, Nor Shazana; Che Saad, Ummi Nadzirah; Ahmad Shukri, Najaa Athirah; Soffian, Sofia Alia Natasya (2020)
To established our business focus. With this business plan, it really helps us to set our goals for what we want to achieve later in the future. Secure our company’s funding. When we set our goals, this helps us to see everything more clearly. We can start planning our company’s funding and this will also help us to be a well prepare company in the future.